The mechanics of wound closure for laparoscopic surgery - Lyons, Mathew (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2014)
The increase in popularity of laparoscopic surgery over the past 25 years has led to a greater importance of reducing the incidence of complications associated with the surgery. Development of a hernia at a trocar port site is a serious complication with a 1-3% incidence that often results in additional surgery for the patient. There is evidence that the occurrence of a hernia is related to the quality of the wound closure, with an absence of closure being a significant risk factor for the development of a hernia. There is also evidence that a mesh-based, tension-free repair of herniae results in fewer complications than suture repair but there has been limited study on the nature of closure failure or methods to improve it. Methodical design of a novel closure method, using a tension-free mesh approach that will reduce the incidence of hernia formation requires a fundamental understanding of the abdominal environment and requires facilities to test concepts and prototypes. To achieve this, an experimental rig representing the abdomen has been developed that incorporates an ability to generate intra-abdominal pressure. This rig can hold either real porcine small intestine or a surrogate material and a real porcine abdominal wall or a surrogate. Simulating an intra-abdominal pressure in the rig causes the intestine to extrude through the abdominal wall, similar to the formation of a hernia following laparoscopic surgery. A surrogate small intestine material has been developed by examining the extrusion properties of porcine small intestine and a number of potential surrogate materials. Reconstituted powdered potato was selected as the most suitable surrogate material that accurately replicates the extrusion properties of small intestine and can be used in the surrogate abdomen rig. A fundamental mathematical and analytical understanding of the mechanics and physiology of hernia formation has also been developed and provides a clear understanding of the root cause of the problem of trocar site herniae and of intra-abdominal pressure. There is limited literature on the structural properties of the abdominal wall, particularly the rectus sheath, which has been shown to be implicated in ventral incisional herniae. A detailed analysis of the uniaxial and biaxial structural properties of the rectus sheath is presented. It was found that the response of porcine rectus sheath to uniaxial loading is similar to human rectus sheath, permitting the use of a porcine model in herniae investigations. Comprehensive stress-stretch plots are also presented which could allow future development of a surrogate abdominal wall for surgical device testing. The surrogate abdomen rig was partially validated against data from a small observational study of surgical patients. The rig was found to perform well, with hernia generation at pressures similar to those realised physiologically and RPP again proving to be a suitable surrogate for real small intestine. Additionally, a quadratic relationship was established between the pressure required to initiate a hernia and the diameter of the defect. This quadratic relationship was further developed in an examination of mesh overlap requirements for defect closure. With limited literature on the ideal mesh overlap, and current practice likely to be over-estimating the mesh size required, the surrogate abdomen model was employed in a preliminary study to develop a mesh and defect size relationship. Similar to the findings of the rig validation study, it was found that the relationship between mesh diameter, defect diameter and hernia generation pressure is quadratic, explained by the relationship between pressure, force and area. A mathematical formula developed to predict the required mesh size was found to under-perform due to the complexity of the interaction with tacks used to secure the mesh, however a novel empirical model recommended a mesh twice the hole diameter plus an additional 25mm. In conclusion, a detailed understanding of the intra-abdominal pressure environment has been developed through fundamental analysis of the physiological processes and tissues involved. This understanding has been used to develop a novel surrogate abdomen environment in which new abdominal surgery devices and techniques can be tested with the aim of reducing the incidence of post-operative complications.
Keywords: Bioengineering, Ph.D.; Ph.D. Trinity College Dublin